2021
DOI: 10.32350/jfar.0301.01
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Financial Leverage on Financial Sustainabilit: A Case of A Microfinance Institution in Kenya

Abstract: Microfinance institution plays a crucial role in economic development and financial inclusion. Financial sustainability is the key dimension to microfinance institutions growth. Which further indicate the importance of which Financial sustainability is. Therefore, the present study investigated the effect of financial leverage on MFI financial sustainability. The specific objective was to establish the effect of financial leverage on the financial sustainability of MFIs. The study was guided by agency theory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Financing choice is vital to every firm as the optimal financial leverage between debt and equity impacts on the firm's valuation and its stock prices in the securities market. Bitok, Cheboi and Kemboi (2021)) indicated that short term debt equity ratio significantly affects return on assets (ROA), return on equity (ROE) and return on capital employed (ROCE). Equity has a positive and significant relationship with ROE and ROCE.…”
Section: Introductionmentioning
confidence: 99%
“…Financing choice is vital to every firm as the optimal financial leverage between debt and equity impacts on the firm's valuation and its stock prices in the securities market. Bitok, Cheboi and Kemboi (2021)) indicated that short term debt equity ratio significantly affects return on assets (ROA), return on equity (ROE) and return on capital employed (ROCE). Equity has a positive and significant relationship with ROE and ROCE.…”
Section: Introductionmentioning
confidence: 99%